Avian Louse Flies and Their Trypanosomes: New Vectors, New Lineages and Host-Parasite Associations - Santolíková, Anežka; Brzoňová, Jana; Čepička, Ivan; Svobodová, Milena (Microorganisms, 2022)
Louse flies (Hippoboscidae) are permanent ectoparasites of birds and mammals. They have a cosmopolitan distribution with more than 200 described species. The aim of this study was to reveal host-vector-parasite associations between louse flies, birds, and trypanosomes. A total of 567 louse fly specimens belonging to 7 species were collected from birds at several localities in Czechia, including the rare species Ornithophila metallica and Ornithoica turdi. There was a significant difference in the occurrence of Ornithomya avicularia and Ornithomya fringillina on bird hosts according to their migratory status, O. fringillina being found more frequently on long-distance migrants. Trypanosomes were found in four species, namely, Ornithomya avicularia, O. fringillina, O. biloba, and Ornithoica turdi; the later three species are identified in this paper as natural trypanosome vectors for the first time. The prevalence of trypanosomes ranged between 5 and 19%, the highest being in O. biloba and the lowest being in O. fringillina. Phylogenetic analysis of the SSU rRNA gene revealed that a vast majority of trypanosomes from hippoboscids belong to the avian T. corvi/culicavium group B. Four new lineages were revealed in group B, with louse flies being probable vectors for some of these trypanosome lineages. We also confirmed the transcontinental distribution of several trypanosome lineages. Our results show that hippoboscids of several genera are probable vectors of avian trypanosomes.
Keywords: Ornithophila; Ornithomya; Trypanosoma; Hippoboscidae; avian parasite; transmission; host specificity; Ornithoica